Solo Living During the Covid-19 Pandemic: International Sociological Research Experience - Yashkina, Daria (Ukrainian Sociological Journal, 2021)
The present paper concerns the research related to solo life during the COVID-19 pandemic and the resulting quarantine restrictions in different countries around the world. The definition of the concept of "solo life" is given, and the corresponding phenomenon is analyzed. Taking into account the existing publications about solo living in a pandemic, the main problems that its representatives may face are highlighted, namely: problems of social well-being, problems of perception and compliance with quarantine restrictions, problems of employment and labor relations, physical isolation and problems of finding romantic relationships. The ways to overcome these problems are considered, in particular, such as creating "bubbles" of communication, intensifying communication with relatives, friends, and colleagues. The most appropriate research methods for the specified social group are determined. It is concluded that there is a need for a comprehensive study of solo living using both quantitative and qualitative methods. Such limitations of using the data of the analysis carried out as insufficient development of the categorical apparatus, which causes difficulties in comparing the results of various studies, are outlined; focus on the problems of women who adhere to the solo lifestyle; differences in the implementation of quarantine measures in different countries and monitoring their compliance. Despite the fact that most of the countries where the analyzed studies were conducted are socially and economically more developed than Ukraine, it is proved that in our country some of the listed problems may be deeper: new difficulties may arise due to the situation in the post-Soviet space. The range of issues that update the study of solo living in Ukraine during the pandemic is determined, namely: the problems of single elderly people; the economic situation of people living solo; the ineffectiveness of social policies aimed at supporting solo individuals. It is concluded that the main issue in the study of solo living in Ukraine is the determination of its socio-cultural specifics.